THE QUALITY OF LIFE OF BREAST CANCER PATIENTS WITH CHEMOTHERAPY: A PHENOMENOLOGY STUDY - Fajar Firdaus A; Neni Nuraeni; Hani Handayani (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2018)
Breast cancer patients experience physical and psychological changes. Psychic changes include sadness, worry, and fear related to the future and death. This psychological change would affect the quality of life. Data in the SMC Hospital Tasikmalaya District in 2017, the number of cancer cases reached 142, and 75% of them were stadium II and III with therapy namely chemotherapy. This study aimed to explore more deeply the quality of life of patients with cancer mammae who had chemotherapy. This qualitative research applied the phenomenology approach. Participants were selected by purposive sampling technique, 4 patients participated in this study. Data were analyzed by Collaizi methods. The results of the study found themes including the causes of physical limitations of breast cancer sufferers, sleep disorders of breast cancer patients, psychological problems of breast cancer sufferers and sexual relations of breast cancer sufferers. Nurses are advised to provide motivation and support for breast cancer patients by providing optimal nursing care to improve the quality of life of patients.Keywords: Breast cancer, hope, Quality of life